Investigation the Relationship Between Body Mass Index and Mortality in COVID-19 Patients - BOLUKÇU, SİBEL; BOLUKÇU, SİBEL; ÖZMEN, MEHMET EMİN; ÖZMEN, MEHMET EMİN; EKŞİ, ÇAĞLA; EKŞİ, ÇAĞLA; OKAY, GÜLAY; OKAY, GÜLAY; SÜMBÜL, BİLGE; SÜMBÜL, BİLGE; KAÇMAZ, ASİYE BAHAR; KAÇMAZ, ASİYE BAHAR; et al. (My University, 2021)
Objective: Obesity might be a risk factor for patients with Coronavirus disease-19 (COVID-19). We aimed to investigate the association of the obesity with intensive care need and mortality caused by severe acute respiratory syndrome-CoV-2 (SARS-CoV-2) infection in this retrospective cohort. Methods: Between March 11th and May 1st, 135 patients, who were treated in our clinic, were enrolled in the study. Body mass index (BMIs) of the patients were grouped according as WHO criteria (<25 kg/m(2): normal, 25 30 kg/m(2): overweight, >30 kg/m(2): obese). Results: Of our patients, 34.1% (n=46) were obese. Mean BM! of the mortality group was 31.2 kg/m(2) and was not different from that of the survivors (p=0.09), However, mean BMI of the patients, in whom intensive care was needed, teas 31.2 kg/m(2) and higher than that of those intensive care was nut needed (p=0.04). In subgroup analyses, obesity (BMI >31) kg/m(2)) was more common among mortality group versus survivors in males older than 60 years old (p=0.03). Conclusion: Obesity with associated disorders are negative prognostic factors for COVID-19 and should be tackled as the end of the pandemic is obscure.
Keywords: COVID-19; obesity; Turkey